An analysis of the performance determinants of modern pentathlon athletes in laser-run, a newly-combined event in modern pentathlon - Lim, C.-H.; Yoon, J.-R.; Jeong, C.-S.; Kim, Y.-S. (Exercise Science, 2018)
PURPOSE: Modern pentathlon, a combined athletic event, where final scores represent the aggregate of scores from swimming, fencing, horseback riding, and laser-run (running and shooting combined), requires participating athletes to have a wide range of athletic prowess, including cardiovascular endurance, agility, muscle power, and muscle strength. Thus, this study analyzed the predominant determinants of athletic performance in the new laser-run event by comparing elite and non-elite athletes. METHODS: Athletes were divided into two groups, elite athletes (n=7, 19.33±0.52 years, BMI=22.18±0.59) and non-elite athletes (n=7, 19.33±0.82 years, BMI=22.27±1.1). For each athlete, a range of metabolic parameters were measured with a wireless respiratory gas analyzer during conducting laser-run. We also determined the overall performance in the laser-run event, including shooting time, accuracy, delay per shooting attempt, and running speed for each phase. RESULTS: The elite group took significantly less time to complete the event than the non-elite group (11 ´ ´47 ´13, and 12 ´ ´20 ´17, respectively; p=.015). Data revealed that even in shooting and running, most elements have an association with athletic performance, but running time and speed during each phase and overall showed a significant difference between groups (p < .05). CONCLUSIONS: Our data indicate that determining factors in the shooting and running phase have a close relationship with overall event performance. However, running time and speed during the running phase rather than the shooting phase were identified as being the most important determinants. Thus, reducing the time lapse during the running phase by improving cardiovascular endurance and endurance exercise capacity is highly recommended.